Revitalisasi Pendidikan Pancasila: Upaya Membentuk Karakter Generasi Z yang Beretika dan Berintegritas - Nazila Aufa Syifa; Ammar Dani; Al ikhsan Keisya; Zaenul Slam (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2026)
This study aims to reaffirm and revitalize the values of Pancasila that have gradually declined in the modern era. Generation Z in order to build a character that has integrity and as a strong foundation for the values of Pancasila in the context of globalization. This article describes the role, implementation, and actualization of the values contained in each element of Pancasila to increase the spirit of development and advance the nation, strengthen resilience to the impacts of globalization and digital flows, and encourage active involvement in national development and produce a generation that thinks critically with the moral foundation of Pancasila. This study adopts a qualitative This study applies a literature review approach by gathering data and utilizing references from credible previous studies, including sources such as books, academic journals, newspapers, and magazines. The collected information is then analyzed and presented in a descriptive manner. Revitalizing Pancasila education is very important for dealing with the challenges that globalization and digital changes bring to Generation Z. Pancasila values should be used more as rules for good behavior and moral choices in everyday life. Pancasila education can also help create a Generation Z that has clear goals, strong ethics, and deep awareness of social issues.